2015
DOI: 10.1071/ah14118
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning in palliative care: a national survey of health professionals and service managers

Abstract: Objective. To identify the attitudes, knowledge and practices regarding advance care planning (ACP) in palliative care.Methods. A nationwide online survey was distributed to Australian palliative care services associated with the Palliative Care Outcomes Collaboration (n = 105). Seventy-three health professionals (HPs) and 59 service managers completed the survey.Results. Regarding ACP, 51% of service managers reported relevant policies and procedures were in place in their service and 44% included ACP in job … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
(44 reference statements)
1
20
0
Order By: Relevance
“…Further details of the survey and results from the closed questions are provided elsewhere. 6 Consent was implied by completion of the online questionnaire. Ethics approval was obtained from the University of Wollongong/Illawarra Shoalhaven Local Health District Human Research Ethics Committee (Approval no.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further details of the survey and results from the closed questions are provided elsewhere. 6 Consent was implied by completion of the online questionnaire. Ethics approval was obtained from the University of Wollongong/Illawarra Shoalhaven Local Health District Human Research Ethics Committee (Approval no.…”
Section: Methodsmentioning
confidence: 99%
“…7 However, despite the reported benefits, our knowledge of the use of ACDs in the clinical setting is limited, particularly within specialist palliative care services. 6 Specifically, little is known about how ACDs are implemented in palliative care or how advance care plans affect palliative care health professionals' experiences of caring for people at the end of life, especially in the Australian health context. The aim of the present study was to explore service providers' perceptions and experiences of advance care planning and the use of ACDs in Australian palliative care services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As over 50% of Australians die in hospitals, policy and standards encourage hospitals to support ACP [1][2][3][4][5] to improve the quality of end-of-life (EOL) care. [6][7][8][9][10] However, a 2014 review found that ACP documentation is often limited, inaccessible and not associated with improved care quality. Health care improvement organisations advocate that hospitals develop systems to elicit, store and act on patient preferences in a dependable way.…”
Section: Outline Of Problemmentioning
confidence: 99%
“…Previous research surveys on ACP have focused on a single setting (eg, inpatient hospital or primary care), 6,7 a single group of health care providers (eg, only physicians or only palliative care providers), 5,8 specific diseases such as cancer or heart failure, 9 or were conducted outside the United States. 7,10 …”
Section: Introductionmentioning
confidence: 99%